Method Implementation Multifactor Evaluation Process (MFEP) in Recommending the Best Types of Cattle for Beef Cattle Farming - Lise Pujiastuti; Mochamad Wahyudi; Freshtiya Beby Larasati; Solikhun (Jurnal Mantik, 2021)
This study aims to implement a decision support system in recommending the best type of cow. The research data comes from interviews and field observations. Based on these observations and interviews, 5 alternatives were obtained Lemosin (A1), Simental (A2), Bali (A3), Dairy (A4), Brahma (A5), as the selected type of cow and 5 criteria for selecting cattle, namely Origin (A), Price (B), Age (C), Weight (D), and Size (E). This research uses the MFEP (Multi Factor Evaluation Process) method. From the results of research and calculations using the MFEP method, it is found that Lemosin (A1) is the best type of cow with a total weight value of 0.6875.This study aims to implement a decision support system in recommending the best type of cow. The research data comes from interviews and field observations. Based on these observations and interviews, 5 alternatives were obtained Lemosin (A1), Simental (A2), Bali (A3), Dairy (A4), Brahma (A5), as the selected type of cow and 5 criteria for selecting cattle, namely Origin (A), Price (B), Age (C), Weight (D), and Size (E). This research uses the MFEP (Multi Factor Evaluation Process) method. From the results of research and calculations using the MFEP method, it is found that Lemosin (A1) is the best type of cow with a total weight value of 0.6875.